Advances in soils and fertilizers in Japan : (Japanese Society of Soil Science and Plant Nutrition, 1990)
List of content: Problem soils; Converted paddy field; diagnosis and amendment of soil; Diagnosis of plant nutrition and fertilization; damage of continuous cropping; Environmental conservation.